Obstetric and gynecologic ultrasound: - Johnson, Pamela T. (Mosby, 2001)
Part of the popular Case Review series, Obstetric and Gynecologic Ultrasound -- Case Review focuses on obstetric and gynecologic ultrasound, complete with full discussion and images.